The Effect of Employee Well-Being and Leadership Style on Turnover Intention of Generation Z Employees in Pati City (International Journal of Economics and Management Research, 2026)
The dynamic development of the work world increases the mobility of Generation Z employees, including in Pati City. The high turnover intention among this generation presents a challenge for organizations in retaining a young workforce. The imbalance between work demands and psychological well-being, as well as less adaptive leadership styles, demonstrate the importance of employee well-being and leadership style in employee retention strategies. This study aims to analyze the influence of employee well-being and leadership style on turnover intention among Generation Z employees in Pati City. The study used a quantitative approach with a survey method of 96 respondents selected through accidental and snowball sampling techniques. Data were analyzed using multiple linear regression. The results showed that employee well-being had no significant effect on turnover intention, while leadership style had a negative and significant effect. Simultaneously, both variables had a significant effect with an Adjusted R Square value of 18.7%. This finding confirms that strengthening leadership quality is a key strategy in reducing turnover intention, accompanied by efforts to continuously improve work well-being.